Plant diversity patterns in remnant forests and exotic tree species‐based reforestation in active limestones quarries in the Luzon and Mindanao biogeographic sub‐regions in the Philippines. Issue 1 (20th November 2017) - Galindon, John Michael; Pasion, Bonifacio; Tongco, Ma. Dolores; Fidelino, Jay; Duya, Mariano Roy; Ong, Perry
Abstract: The Philippines is both a megadiversity country and a global biodiversity hotspot. The diversity patterns of three major plant groups were assessed: (1) trees (trees and palms), (2) herbs (grasses, shrubs, forbs, ferns), and (3) epiphytes (climbers and epiphytes), by determining the changes in compositional and species richness patterns in two forest conditions, i.e., remnant forests and exotic tree species‐based reforested areas, in active forest over limestone quarries in the Luzon and Mindanao biogeographic sub‐regions of the Philippines. We identified 458 species comprising 266 tree species, 95 herbaceous species and 97 epiphyte species. Of these, 21 species were categorized as threatened species. Species composition differed between remnant forests and exotic tree species‐based reforested areas for tree species and epiphyte species, while composition differences between the Luzon and Mindanao biogeographic sub‐regions were limited to tree species only. Differences in species diversity (in terms of richness) were observed between biogeographic sub‐regions for all plant groups, while differences between forest conditions were found for tree and epiphyte species only. Interestingly, there were significantly fewer numbers of exotic species in bigger remnant forest sites and in older exotic tree species‐based reforested sites, while larger numbers of native species occurred in older than in younger exotic tree species‐based reforested sites. The results emphasize the importance of understanding forest recovery in disturbed ecosystems. Conservation attention should focus on protecting remaining forests and planting native species as part of a forest restoration strategy to enhance faster forest recovery and re‐connecting remnant forest patches.